The Birth of Illegitimate Children According to Islamic Law and Legislation in Brunei Darussalam - binti Haji Matnor, Siti Nur Adibah; Kurniawan, Cecep Soleh (MAQASIDI: Jurnal Syariah dan Hukum, 2024)
A child born out of wedlock, commonly referred to as an illegitimate child or a child of zina, is the result of unlawful sexual intercourse before the establishment of a marital relationship. This issue is increasingly prevalent worldwide, affecting people of all religions and ethnicities. The country of Brunei Darussalam is also not immune to facing cases of syariah crimes, such as premarital pregnancies, which lead to the birth of illegitimate children. Islamic jurists (fuqaha) have different views on the duration of a woman’s pregnancy in determining whether a child can be recognized as legitimate or not. The objectives of this study include understanding the concept of illegitimate children according to Islamic law and the Islamic Family Law (Chapter 217) in Brunei Darussalam, as well as exploring the current situation regarding illegitimate children in the country. Furthermore, this paper will discuss the rights of illegitimate children in terms of nasab (lineage) and inheritance. The methodology used in this study is qualitative, involving the collection of research data from books, journals, articles, and other sources relevant to the topic. Statistical data on the birth of illegitimate children were obtained from the Department of Immigration and National Registration of Brunei. The findings of this study indicate that according to Brunei’s Islamic Family Law, the duration of pregnancy, based on the opinions of jurists other than those of the Maliki school, is 180 days. Statistics on the birth of illegitimate children in Brunei show a significant number of such births. The rights of illegitimate children differ from those of legitimate children, particularly concerning nasab, inheritance, and other related aspects.